Synthesis and characterization of CoxNi1‐xFe2O4 samples by solution combustion method using glycine as fuel. Issue 1 (30th September 2016) - Jithin, P. V.; Baghya, P. K.; Roona, N.; Thomas, Anu; Thomas, Nygil; Sudheesh, V. D.; Sebastain, Varkey; Lakshmi, N.
Abstract : Nano sized Cox Ni1‐x Fe2 O4 (0≤x≤1) samples were prepared by solution combustion method using glycine as fuel, maintaining a fuel to oxidizer ratio of 0.8. PXRD and FTIR analysis confirms the formation of the spinel phase. Non spherical and highly crystalline nature of the sample was revealed by HRTEM analysis. Lattice parameters of all samples calculated after Rietveld refinement and their variation are in accordance with Vegard's law. DC magnetization study indicates a transformation from soft to hard magnetic phase on increase in Co concentration. Saturation magnetization of nickel ferrite samples match well with that of bulk samples, while the pure cobalt ferrite sample has a lower saturation magnetization compared to that of the bulk, which may be due to spin canting. Impedance measurements of the samples give general trend shown by ferrite material which is in accordance with Koop's phenomenological theory. The study shows that the magnetic and electric properties of nickel ferrite nanoparticles can be easily tailored using a simple solution combustion method in the fuel lean condition with glycine as fuel.